Synthesis and esr studies of a soluble vanadyl porphyrazine - Öztürk, Ramazan; Güner, Sadik; Aktas, Bekir; Gül, Ahmet (Informa UK Limited, 2001)
Octakis(hexylthio)vanadyl porphyrazinate, (VOPz), was prepared from vanadyl(IV) sulfate and metal-free porphyrazine (H2Pz), which was synthesized by the cyclotetramerization of the corresponding dinitrile derivative and further treatment with trifluoroacetic acid. Intense absorption peaks at 699 and 352 nm in the electronic spectrum indicated the C4v symmetry of VOPz. ESR studies, both in solution and in powder form, confirmed the proposed structure.